Metal-Free Photoredox Catalyzed Sulfonylation of Phenylhydrazines with Thiols - Kushwaha A.K.; Kamal A.; Kumari P.; Singh S. (My University, 2025)
The sulfonylation method stands out as a simple and efficient approach for synthesizing sulfonamides. Despite the advancements in constructing the sulfonamide framework, the potential use of phenyl hydrazine as an amination source remains unexplored. Herein, we report a metal-free, environment-friendly photoredox-catalyzed sulfonylation of phenylhydrazines using thiols, employing MeCN:H2O as a green solvent and eosin Y as a photoredox catalyst. This strategy exhibits a broad substrate scope and good functional group compatibility, including hetero(aryl) as well as aliphatic phenylhydrazines. Finally, this protocol also demonstrated good application for the synthesis of pharmaceutical analogues. © 2024 American Chemical Society.